2007
DOI: 10.1109/tac.2007.892383
|View full text |Cite
|
Sign up to set email alerts
|

Itô–Volterra Optimal State Estimation With Continuous, Multirate, Randomly Sampled, and Delayed Measurements

Abstract: The optimal filter for continuous, linear, stochastic, time-varying systems described by the Itô-Volterra equations with discontinuous measure is derived. With an appropriately selected measure, the result is applicable to a wide range of observation processes, including the hybrid case of observations formed by an arbitrary combination of continuous and discrete measurements, which may be sampled with a priori unknown, changing, and, possibly, random rates and delays. The simultaneous presence of continuous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 30 publications
0
57
0
Order By: Relevance
“…In this section, by resorting to the Lyapunov functional method and the stochastic analysis technique, sufficient conditions are provided to guarantee the stability and the H ∞ performance for the closed-loop systems (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, by resorting to the Lyapunov functional method and the stochastic analysis technique, sufficient conditions are provided to guarantee the stability and the H ∞ performance for the closed-loop systems (6).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the system (6) is stochastically stable. Let us now move to the analysis of the H ∞ performance for the system (6). For this purpose, we establish a cost function…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Left multiply For the process model (8) and measurement model (4) with the system parameter (9), we use the Kalman filter to get the estimate of system state at every sampling time as follows:…”
Section: Estimation Methods Under Irregular Samplingmentioning
confidence: 99%
“…The complete classification of the "general situation" cases (this means that there are no special assumptions on the structure of state and observation equations and the initial conditions), where the nonlinear finite-dimensional filter exists, is given in Yau (1994). There also exists an extensive bibliography on robust, in particular, H ∞ filtering for linear (Xu and Chen (2003), Mahmoud and Shi (2003) and Xu et al (2005)) and nonlinear (Xie et al (1996), Nguang and Fu (1996), Fridman and Shaked (1997), Shi (1998), Fleming and McEneaney (2001), Yaz and Yaz (2001), Xu and van Dooren (2002), Wang et al (2003), Gao and Wang (2004), Zhang et al (2005), Gao et al (2005), Zhang et al (2007), Gao and Chen (2007), Wang et al (2008), Wang et al (2009), Wei et al (2009) and Shen et al (2009)) stochas-tic systems. Apart form the "general situation," the mean-square finite-dimensional filters have been designed for certain classes of polynomial system states with Gaussian noises over linear observations (Basin (2008), Basin et al (2008) and Basin et al (2009)) and a few results related to nonlinear Poisson systems can be found in Lu et al (2001), Kolmanovsky and Maizenberg (2002a), Hannequin and Mas (2002), Kolmanovsky and Maizenberg (2002b), Zhang et al (2008a), Dupé et al (2008), Zhang et al (2008b), and Basin and Maldonado (2011).…”
Section: Introductionmentioning
confidence: 99%